Synthesis of Some 4'-Amino Chalcones and their Antiinflammatory and Antimicrobial Activity - Rajendra Prasad, Y.; Srinivasa Rao, A.; Rambabu, R. (Asian Journal of Chemistry, 2010)
A series of some 4'-amino chalcones were synthesized by Claisen- Schmidt condensation of 4-amino acetophenone with various substituted aromatic aldehydes. The synthesized chalcones were characterized by IR, 1H NMR and elemental analyses. When these chalcones (3a-h) were evaluated for antiinflammatory, antibacterial and antifungal activities, some of them found to possess significant biological activity when compared to standard drugs.